2021
DOI: 10.1038/s41550-021-01381-5
|View full text |Cite
|
Sign up to set email alerts
|

Transit detection of the long-period volatile-rich super-Earth ν2 Lupi d with CHEOPS

Abstract: Parameters Values Star ν 2 Lupi Effective temperature, T eff (K) 5664 ± 61 Log surface gravity, log g (cgs) 4.39 ± 0.11 Microturbulence, ξ t (km/s) 0.85 ± 0.02 Metallicity, [M/H] (dex) −0.24 ± 0.05 Radius, R (R ) 1.058 ± 0.019 Mass, M (M ) 0.87 ± 0.04 Density, ρ (ρ ) 0.734 ± 0.053 Age (Gyr) 12.3 +1.2 −2.9 Rotation period, a P rot (days) 23.8 ± 3.1 Luminosity, L (L ) 1.038 ± 0.059 Planets b c d Orbital period, P (days) 11.57797 +0.00008 −0.00013 27.59221 ± 0.00011 107.245 ± 0.050 Mid-transit time, T 0 (BJD TDB … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 145 publications
2
54
0
Order By: Relevance
“…CHEOPS met its precision requirements both on bright and faint stars, achieving a noise level of ∼ 15 ppm per 6 h intervals for 𝑉 ∼ 9 mag stars, and 75 ppm per 3 h for 𝑉 ∼ 12 mag stars (Benz et al 2021). The importance of such a high photometric precision is reflected in CHEOPS' first scientific results, which span a variety of different fields (Lendl et al 2020;Bonfanti et al 2021b;Leleu et al 2021;Delrez et al 2021;Morris et al 2021a;Borsato et al 2021;Van Grootel et al 2021;Szabó et al 2021;Hooton et al 2021;Swayne et al 2021;Maxted et al 2021;Barros et al 2022;Wilson et al 2022;Deline et al 2022). As part of its main scientific goals, CHEOPS is refining the radii of known exoplanets to achieve the precision on the bulk density needed for internal structure and atmospheric evolution modelling.…”
Section: Introductionmentioning
confidence: 99%
“…CHEOPS met its precision requirements both on bright and faint stars, achieving a noise level of ∼ 15 ppm per 6 h intervals for 𝑉 ∼ 9 mag stars, and 75 ppm per 3 h for 𝑉 ∼ 12 mag stars (Benz et al 2021). The importance of such a high photometric precision is reflected in CHEOPS' first scientific results, which span a variety of different fields (Lendl et al 2020;Bonfanti et al 2021b;Leleu et al 2021;Delrez et al 2021;Morris et al 2021a;Borsato et al 2021;Van Grootel et al 2021;Szabó et al 2021;Hooton et al 2021;Swayne et al 2021;Maxted et al 2021;Barros et al 2022;Wilson et al 2022;Deline et al 2022). As part of its main scientific goals, CHEOPS is refining the radii of known exoplanets to achieve the precision on the bulk density needed for internal structure and atmospheric evolution modelling.…”
Section: Introductionmentioning
confidence: 99%
“…CHEOPS met its precision requirements both on bright and faint stars, achieving a noise level of ∼ 15 ppm per 6 h intervals for ∼ 9 mag stars, and 75 ppm per 3 h for ∼ 12 mag stars (Benz et al 2021). The importance of such a high photometric precision is reflected in CHEOPS' first scientific results, which span a variety of different fields (Lendl et al 2020;Bonfanti et al 2021b;Leleu et al 2021;Delrez et al 2021;Morris et al 2021a;Borsato et al 2021;Van Grootel et al 2021;Szabó et al 2021;Hooton et al 2021;Swayne et al 2021;Maxted et al 2021;Barros et al 2022;Wilson et al 2022;Deline et al 2022).…”
mentioning
confidence: 99%
“…Several studies (e.g. Lendl et al 2020;Bonfanti et al 2021;Delrez et al 2021;Leleu et al 2021) have found success in removing these systematics by conducting a linear decorrelation using several basis vectors, such as background, contamination, orbital roll angle, and 𝑥 and 𝑦 centroid positions. Upon inspection of the CHEOPS observations of TOI-1064, we found significant flux variations on orbital timescales.…”
Section: Cheopsmentioning
confidence: 99%
“…After rejecting those thats do not fulfil the constraint imposed by the present-day atmospheric content derived in Section 5.1, we obtained the posterior distributions of the free parameters. Further details about the tool may be found in Delrez et al (2021). The results of the joint evolution of both planet b and c are shown in Figs.…”
Section: Atmospheric Evolutionmentioning
confidence: 99%
See 1 more Smart Citation